Comparison of the Morphology Development of Polymer–Fullerene and Polymer–Polymer Solar Cells during Solution‐Shearing Blade Coating. Issue 22 (22nd August 2016) - Gu, Xiaodan; Yan, Hongping; Kurosawa, Tadanori; Schroeder, Bob C.; Gu, Kevin L.; Zhou, Yan; To, John W. F.; Oosterhout, Stefan D.; Savikhin, Victoria; Molina‐Lopez, Francisco; Tassone, Christopher J.; Mannsfeld, Stefan C. B.; et al.
Abstract : In this work, the detailed morphology studies of polymer poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT):fullerene(PCBM) and polymer(P3HT):polymer naphthalene diimide thiophene (PNDIT) solar cell are presented to understand the challenge for getting high performance all‐polymer solar cells. The in situ X‐ray scattering and optical interferometry and ex situ hard and soft X‐ray scattering and imaging techniques are used to characterize the bulk heterojunction (BHJ) ink during drying and in dried state. The crystallization of P3HT polymers in P3HT:PCBM bulk heterojunction shows very different behavior compared to that of P3HT:PNDIT BHJ due to different mobilities of P3HT in the donor:acceptor glass. Supplemented by the ex situ grazing incidence X‐ray diffraction and soft X‐ray scattering, PNDIT has a lower tendency to form a mixed phase with P3HT than PCBM, which may be the key to inhibit the donor polymer crystallization process, thus creating preferred small phase separation between the donor and acceptor polymer. Abstract : The morphology development of polymer:fullerene and polymer:polymer solar cells is characterized by real‐time X‐ray scattering and interferometry. Polymer:fullerence blends show a smaller phase‐separation due to high glass‐transition temperature of PCBM acceptors, compared to polymer:polymer blends.